KAJIAN EMPIRIS : AGRESIVITAS PAJAK DAN FAKTOR-FAKTOR PENENTUNYA PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ardiani Ika Sulistyawati; Adhitya Hendra; Aprih Santoso (BBM (Buletin Bisnis & Manajemen), 2021)
The purpose of this study is to examine the effect of liquidity, capital intensity, inventory intensity and firm size on tax aggressiveness. The variables used in this study are liquidity, capital intensity, inventory intensity and company size. while the dependent variable in this study is tax aggressiveness measured using ETR. The population taken as the object of this study amounted to 19 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. The observation period is carried out for 5 years. Determination of the study sample using a purposive sampling method and obtaining a sample of 40 based on certain criteria. Data were analyzed using a multiple linear regression analysis model using SPSS 22. The results of the study show that the size of the company influences tax aggressiveness. While Liquidity, capital intensity, inventory intensity does not affect the tax aggressiveness.